PENGARUH FASILITAS KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN: (STUDI KASUS PADA DEPARTEMEN UNIT 1 PT. MERSIFARMA SUKABUMI) - Sobar, Agus (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
This study aims to determine the extent to which work facilities and work environment influence employee performance at PT. Mersifarma Sukabumi. Data were collected through questionnaire and documentation techniques. The research method used was quantitative, with 68 respondents taken using saturated or census sampling techniques. Data analysis in this study used SPSS version 23.00. The results of the t-test showed that the work facilities variable had a positive effect on employee performance, where the t-count value (1.872)> t table (1.668). The work environment had a positive effect on employee performance, as seen from the t-count value (1.904)> t table (1.668). The results of the F test showed that work facilities and work environment together had a positive effect on employee performance of 25.939> F table 3.14 and a significance level of 0.000 <0.05. The R square value of 0.444 or 44.4% means that variations in employee performance can be explained by the work facilities and work environment variables by 44.4%, while the remaining 55.6% is explained by other variables not examined in this study.